Chemicals efficience on the control of the pink bollworm, using a new experimental methodology - Fornazier, Mauricio José; Nakano, Octávio (Pesquisa Agropecuaria Brasileira, 2014)
Two experiments were carried out in the region of Tietê, State of São Paulo, Brazil, in order to test chemicals and a new methodology to conduct field experiments to control the pink bollworm. It were used thirteen and six treatments. The new methodology was based in a pre-evaluation realized at each plot and so it was made a distribution of the treatments in the blocks, defined by infestation intervals. Before the spray, a statistical analysis was made in this pre-evaluation and no significance was found. The evaluation was made by counting attacked and healthy cotton (Gossypium hirsutum L.) bolls, 20 bolls per plot. The results showed that bifenate (50 and 40 g a.i./ha), cypermethrin (50 g.a.i./ha) and permethrin (100 g.i./ha) were the best chemicals tested to control the pink bollworm and that the new methodology may be used to compair chemicals efficiency on the control for this pest.